Normobaric Hyperoxia Therapy in Treating Stroke - Duan Y; Li X; Han S; Guan J; Chen Z; Li W; Meng R; Ding J (Clinical Interventions in Aging)
Yanli Duan,1,* Xiangyu Li,2,* Song Han,1 Jingwei Guan,1 Zhiying Chen,3 Weili Li,4 Ran Meng,5 Jiayue Ding1 1Department of Neurology, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 2Department of Neurology, Tianjin Huanhu Hospital, Tianjin, People’s Republic of China; 3Department of Neurology, Affiliated Hospital of Jiujiang University, Jiujiang, Jiangxi, People’s Republic of China; 4Department of Neurology, The First Affiliated Hospital of Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 5Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiayue Ding, Department of Neurology, Tianjin Medical University General Hospital, No. 154 Anshan Street, Heping District, Tianjin, 300052, People’s Republic of China, Email sjnkzz2@163.comAbstract: Normobaric hyperoxia (NBO) is a standard oxygenation intervention for various conditions/diseases including stroke. The present review summarizes the current literature addressing the neuroprotective mechanisms of NBO in acute ischemic stroke (AIS), intracranial hemorrhage, and chronic cerebral ischemia, as well as its combination with other therapies to identify a more appropriate and effective NBO treatment method and to benefit more patients in clinical settings. The primary mechanism of action of NBO is the elevation of the interstitial partial pressure of oxygen in arterial blood (PaO2) in brain tissue. NBO preconditioning yields moderate production of free radicals before AIS, which can increase antioxidant enzyme production, alter mitochondrial membrane lipids, increase tumor necrosis factor-alpha (TNF-α) converting enzyme levels, stimulate the hypoxia-inducible factor signaling pathway, upregulate glutamate transporters, Na+–Ca+ exchanger, and the metabotropic glutamate receptor after AIS, thus conferring neuroprotection to brain tissue. NBO postconditioning benefits AIS by protecting the penumbra and extending the recanalization time window, indicating that reperfusion is critical for the beneficial effects of NBO. Some previous clinical trials have obtained negative results because they enrolled non-reperfused cohorts. Given penumbra protection, NBO can enhance the efficacy of recanalization therapy, including thrombolysis and endovascular treatment. Clinical studies have indicated that NBO benefits only patients with reperfusion, which is consistent with animal-based research. NBO combined with medications, such as ethanol, minocycline, and edaravone, can more effectively treat AIS than NBO alone. Moreover, NBO demonstrates promise for the treatment of intracranial hemorrhage and chronic cerebral ischemia. NBO is a safe and effective therapy for stroke; however, eligible populations should be restricted to those with penumbra or ischemic and hypoxic brain tissues.Keywords: normobaric hyperoxia, ischemic stroke, hemorrhagic stroke, penumbra